Systemic inflammatory and oxidative stress biomarkers as predictors of pain in sequential bilateral phacoemulsification for age-related cataract - Yin, Peng; Wang, Liyuan; Hou, Yongsheng; Huang, Yang; Sun, Dawei; Shao, Dewang (Frontiers in Medicine, 2025)
BackgroundSecond-eye cataract surgery is frequently associated with enhanced pain perception compared to first-eye procedures, yet the underlying pathophysiological mechanisms remain incompletely understood. This study investigated whether systemic inflammatory biomarkers and oxidative stress indicators could predict and explain the differential pain experience in sequential bilateral phacoemulsification for age-related cataract.MethodsIn this prospective, single-blinded case-control study, we enrolled 80 patients with age-related cataract undergoing sequential bilateral phacoemulsification. Patients underwent first-eye surgery followed by second-eye surgery within a median interval of 2.5 months (range: 1–3 months). Matching was performed using propensity score matching based on age (±2 years), gender, diabetes status (HbA1c levels), and hypertension status (blood pressure measurements). Inflammatory biomarkers, including neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), C-reactive protein (CRP), interleukin-6 (IL-6), interleukin-8 (IL-8), and the oxidative stress marker superoxide dismutase (SOD), were analyzed in preoperative blood samples. Postoperative pain was evaluated 24 h after surgery using the visual analog scale (VAS). A novel cataract pain prediction model, along with correlation analysis and receiver operating characteristic (ROC) curves, was developed to assess the diagnostic and predictive value of these biomarkers.ResultsThe second-eye surgery group demonstrated significantly elevated levels of systemic inflammatory markers (NLR, MLR, CRP, IL-6, and IL-8) and oxidative stress indicator (SOD) compared to first-eye patients (all P < 0.05). VAS pain scores were notably higher in the second-eye group compared to the first-eye group (1.99 ± 1.42 vs. 0.82 ± 0.86, P < 0.001). Significant positive correlations were observed between VAS scores and NLR (r = 0.489, 95% CI: 0.315–0.632, P < 0.001), MLR (r = 0.385, 95% CI: 0.193–0.548, P < 0.001), CRP (r = 0.284, 95% CI: 0.082–0.464, P < 0.001), and SOD (r = 0.334, 95% CI: 0.136–0.507, P < 0.001). ROC analysis confirmed the diagnostic value of these biomarkers for predicting enhanced postoperative pain [area under the curve (AUCs): NLR = 0.800, MLR = 0.737, CRP = 0.669, SOD = 0.718; all P < 0.05]. A multivariate prediction model incorporating these biomarkers achieved superior discriminative ability (AUC = 0.812, P < 0.001).ConclusionThis study demonstrates a significant association between increased systemic inflammatory biomarkers, oxidative stress indicators, and heightened pain perception in second-eye cataract surgery. Our findings provide valuable insights into the pathophysiological mechanisms underlying the second-eye phenomenon and offer potential clinical biomarkers for preoperative pain risk stratification. Implementation of these biomarkers could guide personalized analgesic strategies and improve patient care in sequential bilateral cataract surgery.